Surface-Enhanced Raman Spectroscopy Chips Based on Silver Coated Gold Nanostars - Miriam Parmigiani; Benedetta Albini; Giovanni Pellegrini; Marco Genovesi; Lorenzo De Vita; Piersandro Pallavicini; Giacomo Dacarro; Pietro Galinetto; Angelo Taglietti (Nanomaterials, 2022)
Surface-enhanced Raman scattering (SERS) is becoming widely used as an analytical tool, and the search for stable and highly responsive SERS substrates able to give ultralow detection of pollutants is a current challenge. In this paper we boosted the SERS response of Gold nanostars (GNS) demonstrating that their coating with a layer of silver having a proper thickness produces a 7-fold increase in SERS signals. Glass supported monolayers of these GNS@Ag were then prepared using simple alcoxyliane chemistry, yielding efficient and reproducible SERS chips, which were tested for the detection of molecules representative of different classes of pollutants. Among them, norfloxacin was detected down to 3 ppb, which is one of the lowest limits of detection obtained with this technique for the analyte.